Acute myocardial infarction in pregnancy following unlicensed use of methylenedioxymethamphetamine ('ecstasy'). Issue 3 (August 2013) - Okunoye, GO; Dutton, P
Acute myocardial infarction is rare in pregnancy; however, the emerging trend towards advanced maternal age and the rising prevalence of obesity and diabetes suggest that more cases of myocardial infarction are likely to be encountered in pregnancy. However, there is scanty evidence on the risk of myocardial infarction with regard to socially misused substances in pregnancy. We describe the management of a case of acute myocardial infarction following unlicensed use of 3, 4-methylenedioxymethamphetamine ('Ecstasy') in pregnancy. The case highlights a rare but serious risk associated with substance misuse in pregnancy.